Uzayr's donkey: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
This story tells of Prophet Uzayr, who witnesses the resurrection of his donkey, signifying divine power over life and death. It serves as a reminder of faith and trust in God$1 (Bs will.s